Pomiar rozkładu promieniowego wielkości kropel = The measurement of the radial distribution of droplets size - Krupińska, Andżelika; Ochowiak, Marek; Włodarczak, Sylwia; Markowska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The aim of this paper is to present the measurement methodology using a modified experimental setup allows for the aerosol characteristic determination. The main element of the system is a particle size analyser Spraytec by Malvern Instruments with a PC computer equipped with appropriate software.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne